(untitled) (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2023)
The research presented addresses the topic of technology as the set of techniques for the improvement of activities and its relationship with education, emphasizing financial education, where through the application of a documentary methodology, it develops said study with the objective of enunciating the importance of technology in the educational field, generating a great impact within society, due to the various virtues that its implementation offers from the perspective of understanding assets and liabilities, financial risks and opportunities, and informed decision-making for economic well-being.